2012
DOI: 10.1080/00918369.2012.712817
|View full text |Cite
|
Sign up to set email alerts
|

Confronting Hate: Heterosexuals' Responses to Anti-Gay Comments

Abstract: An online diary study was used to examine the individual and situational variables that influence non-targets' verbal and nonverbal reactions and responses to sexually prejudiced remarks. Results indicated that anti-gay comments were extremely prevalent in a college setting and resulted in a range of reactions and behaviors. Confrontation of the perpetrator was predicted by the perceived offensiveness of the comment, perceived social pressure to confront, and the number of close same-sex attracted friends. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 46 publications
3
47
0
Order By: Relevance
“…However, recent research on non‐targets' responses to heterosexist comments supports the findings in the current study that the perceived offensiveness of the comment is related to confronting behavior (Dickter, ). The perceived offensiveness of the comment may be particularly important to males.…”
Section: Discussionsupporting
confidence: 86%
“…However, recent research on non‐targets' responses to heterosexist comments supports the findings in the current study that the perceived offensiveness of the comment is related to confronting behavior (Dickter, ). The perceived offensiveness of the comment may be particularly important to males.…”
Section: Discussionsupporting
confidence: 86%
“…Majority group members also report hearing an average of four racist comments and three heterosexist comments per week (Dickter & Newton, in press). Much research has suggested that the college campus may be a particularly ripe environment for prejudicial comments and hate speech about various minority groups (Burn, ; D'Augelli & Hershberger, ; Dickter, in press; Dickter & Newton, in press; Plummer, ; Thurlow, ; Swim, Hyers, Cohen, Fitzgerald, & Bylsma, ).…”
mentioning
confidence: 99%
“…Less research has focused on the confrontation of prejudicial comments by non‐target individuals who are majority group members (e.g., White Americans, heterosexuals). Recent work has established that, like targets, non‐targets are reluctant to confront prejudicial remarks because of a fear of being evaluated negatively (Dickter, in press; Dickter & Newton, in press). However, recent work has suggested that non‐targets may not be perceived as complaining when confronting a prejudicial comment that is not directed toward their own group (Czopp & Monteith, ), as target confronters often are (Kaiser & Miller, ).…”
mentioning
confidence: 99%
“…People high in incremental theories of personality react to perpetrators of prejudice by directly stating their point of view and attempting to re-educate the offender (Rattan and Dweck 2010). Self-report research using online diaries also indicates that verbally disagreeing with prejudicial comments is a popular confrontation strategy (Dickter 2012;Dickter and Newton 2013).…”
Section: Prejudice Confrontation Behaviormentioning
confidence: 96%